Study on Thermal-Fluid-Solid Coupling Characteristics for Helicopter Intermediate Spiral Bevel Gear Reducer - Sheng, Dongping; Yang, Jie; Su, Chun (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
In the helicopter transmission system, the intermediate reducer is particularly special. It uses bevel gear pairs to change the transmission direction and to transfer the rotational speed effectively. Therefore, an in-depth study of the spiral gear pair is crucial to improve the overall performance of the helicopter rotor system. This study focuses on the study of the thermal-fluid-solid coupling characteristics and one-way steady-state thermal finite element analysis are conducted based on volume of fluid multiphase flow simulation theory to provide strong support for the design and optimization of the helicopter intermediate reducer. Several conclusions could be obtained. Firstly, it could be found that the negative pressure of the gear engagement occurs and the absolute value increases with the rotation speed of the gear moving wall in the flow field. Secondly, the effect force such as the gear decreases with the increase of the rotational speed of the gear moving wall in the flow field. Thirdly, the contact stress could be affected significantly at different working speed while considering the thermal-fluid influence; Finally, by reasonably controlling the speed of the gear, the stress level between the teeth can be reduced while ensuring the transmission efficiency, as well as improving the service life and reliability of the gear reducer.